Response of bambara groundnut landraces to heat and drought stress in the guinea savanna and transitional zones of Ghana - Opoku, Mathew kwadwo (2015)
Thesis submitted to the School of Postgraduate Studies of Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfilment for the award of Master of Science (Agronomy) degree.